2021
DOI: 10.1016/j.cej.2021.129771
|View full text |Cite
|
Sign up to set email alerts
|

Shelling with MoS2: Functional CuS@MoS2 hybrids as electrocatalysts for the oxygen reduction and hydrogen evolution reactions

Abstract: The development of noble-metal free electrocatalysts is of high importance for clean energy conversion applications. MoS2 has been considered as a promising low-cost catalyst for the hydrogen evolution reaction (HER), however its activity is limited by poor conductivity and low abundance of active sites.Moreover, its suitability as an effective catalyst for other reactions, in particluar the oxygen reduction reaction (ORR), was hardly explored to date. Herein, we show hybrid nanostructures of shelled CuS parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…(6) In addition to the fields of HER/NRR/CO 2 RR activity, in just the past few years, owing to its superior electronic properties and capacities, MoS 2 has also been widely employed in a wide range of applications such as the environmental applications, 222 electrochemical oxygen reduction reaction (ORR), 223 NO reduction, 224 supercapacitors, 225 sensors, 226 secondary batteries ( e.g. , Li-ion batteries (LIBs), 227 Li–S batteries, 228 Li–O 2 batteries, 229 Na–S batteries, 230 Na–O 2 batteries, 231 Mg-ion batteries, 232 Al-ion batteries, 233 and Na-ion batteries, 234 etc.…”
Section: Discussionmentioning
confidence: 99%
“…(6) In addition to the fields of HER/NRR/CO 2 RR activity, in just the past few years, owing to its superior electronic properties and capacities, MoS 2 has also been widely employed in a wide range of applications such as the environmental applications, 222 electrochemical oxygen reduction reaction (ORR), 223 NO reduction, 224 supercapacitors, 225 sensors, 226 secondary batteries ( e.g. , Li-ion batteries (LIBs), 227 Li–S batteries, 228 Li–O 2 batteries, 229 Na–S batteries, 230 Na–O 2 batteries, 231 Mg-ion batteries, 232 Al-ion batteries, 233 and Na-ion batteries, 234 etc.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sadan et al synthesized a functional CuS@MoS 2 hybrid electrocatalyst with an overpotential of 225 mV at 10 mA cm −2 . 114 Liu et al reported a self-healing γ-FeOOH decorated onto MoS 2 nanosheets, which only needed 291 mV overpotential to reach 300 mA cm −2 and kept stable at 100 mA cm −2 for 20 h. 115 Benefiting from the high content of the bridging S 2 2− in MoS 2 and the synergistic effect of MoS 2 , MoO 3 −x, and Ni 3 S 2 , the MoS 2 −MoO 3 −x/Ni 3 S 2 heterostructure exhibited excellent catalytic activity toward the HER in 1.0 M KOH solution with an overpotential of 76 mV at 10 mA cm −2 and an excellent stability over 17 h, which was the best among the reported MoS 2 -based hybrid electrocatalysts for the alkaline HER. 116 In conclusion, construction of heterostructures can optimize the activity of MoS 2 , adjust the electronic structure, accelerate electron transfer, and improve the adsorption free energy.…”
Section: Phase Transitionmentioning
confidence: 99%
“…TMDCs, especially sulfides, [25][26][27] selenides, [28][29][30] and oxides, [31,32] have recently attained tremendous interest as electrocatalysts for water-splitting because of their stability, abundance, and cost-effectiveness. [33,34] In the family of common TMDCs, tungsten is the heaviest one; therefore, controlling its compound properties is easier.…”
Section: Introductionmentioning
confidence: 99%